Cover Feature: Photoactivatable Adhesive Ligands for Light‐Guided Neuronal Growth (ChemBioChem 12/2018). (5th June 2018) - Farrukh, Aleeza; Fan, Wenqiang; Zhao, Shifang; Salierno, Marcelo; Paez, Julieta I.; del Campo, Aránzazu
Abstract : The cover feature picture shows the optoregulation of neuronal growth through the combined use of a photoactivatable biomaterial and light. Soft polyacrylamide hydrogels functionalized with caged laminin‐mimetic peptides are activated upon light irradiation, thereby providing spatial adhesion and differentiation guidance to seeded neurons to grow in predefined patterns. More information can be found in the full paper by J. I. Paez, A. del Campo et al. onpage 1271 in Issue 12, 2018 (DOI:10.1002/cbic.201800118 ).